The scientific problem in original articles published in Cuban biomedical journals - Maicel Eugenio Monzón Pérez; Tania Sánchez-Ferrán; Lazara C. Oviedo Herrera; Ivette Camayd Viera (Universidad de Ciencias Médicas de La Habana, 2018)
Introducción:The formulation of the scientific problem in a research article is a key element for its understanding and reproducibility.  If it is not defined or if it is incorrectly formulated, it would inevitably lead to the creation of a document which would be very difficult to understand and repl Objective:To identify the most common lines of research in Cuban biomedical journals indexed in SciELO, the frequency of research articles with a correctly defined scientific problem, and the most common errors in its formulation. Material and Methods: A descriptive study was carried out in research articles that were published in 2016 in 32 Cuban biomedical journals indexed in SciELO. The most frequent lines of research were obtained from 5 836 keywords.  The percentage of publication with a correctly defined scientific problem was estimated by a random selection of a sample of 50 articles, and the percentage of publications with a correctly defined scientific problem was also calculated. Percentages of errors according to type were measured in each article. Results:The most frequent lines of research associated with keywords were: medical education, risk factors, and secondary health care. Only 36% of the works formulated the scientific problem correctly. No article made a critical assessment of it, and the 58 % included methods to address it. Conclusions:The lines of research identified in the articles under study may appear to be of minor interest for biomedical research. The research articles with not defined or incorrectly formulated scientific problems increase the difficulties for their analysis, discussion, and review of scientific results. The most common errors in the formulation of the scientific problem suggest that the main motivation could not be the dissemination of a scientific result, but the publication itself. Keywords:research question, hypothesis, research project, scientific research, original article.